2016
DOI: 10.1038/srep22235
|View full text |Cite|
|
Sign up to set email alerts
|

Mutation analysis of the phospholamban gene in 315 South Africans with dilated, hypertrophic, peripartum and arrhythmogenic right ventricular cardiomyopathies

Abstract: Cardiomyopathy is an important cause of heart failure in Sub-Saharan Africa, accounting for up to 30% of adult heart failure hospitalisations. This high prevalence poses a challenge in societies without access to resources and interventions essential for disease management. Over 80 genes have been implicated as a cause of cardiomyopathy. Mutations in the phospholamban (PLN) gene are associated with dilated cardiomyopathy (DCM) and severe heart failure. In Africa, the prevalence of PLN mutations in cardiomyopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…In addition, multiple small genotyping studies identified a handful of heterozygous PLN mutations in individuals that were missense. 211, 212 Moreover, PLN mutations have been identified in individuals with HCM exclusively. These include a handful rare PLN promoter have been identified in multiple independent cohorts.…”
Section: Arrhythmias Caused By Heritable Defects In Calcium-handling mentioning
confidence: 99%
“…In addition, multiple small genotyping studies identified a handful of heterozygous PLN mutations in individuals that were missense. 211, 212 Moreover, PLN mutations have been identified in individuals with HCM exclusively. These include a handful rare PLN promoter have been identified in multiple independent cohorts.…”
Section: Arrhythmias Caused By Heritable Defects In Calcium-handling mentioning
confidence: 99%
“…Calcium cycling is abnormal in young PLN R9C/+ mice before the onset of overt cardiac remodeling (denoted as pre-DCM). However, PLN R9C/+ mice subsequently develop DCM that consistently progresses to fulminant HF and premature death, (3) thus recapitulating the chronologic manifestations in human patients with this mutation (35). To delineate the longitudinal consequences of altered calcium homeostasis in cardiac remodeling, we studied the transcriptional changes in cardiomyocytes and nonmyocytes from pre-DCM through DCM to HF.…”
Section: Introductionmentioning
confidence: 99%
“…(5,6) PLN R9C mice display altered calcium handling prior to onset of phenotypic disease (preDCM) and ultimately develop progressive DCM with fulminant heart failure culminating in premature death. (4) This inexorable process mimics the disease course of individuals carrying this mutation (4,7,8) and recapitulates the natural history of DCM.…”
Section: Introductionmentioning
confidence: 61%